Feed Production Training and Floating Net Cage Utilization for Fish Farming at KUPS Fisheries, LPHD Tanjung Sangalang, Pulang Pisau, Central Kalimantan - Ahmad Muammar Kadafi; Awalul Fatiqin; Salsabila Devana Putri; Tio Pinta Agustina Tamba; Dwi Septiana Safira; Agung Samudra; Made Dirgantara; Shinta Sylvia Monalisa; Nuriman Wijaya (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
This article addresses the growing demand for fish products in Indonesia, driven by increased per capita fish consumption, which has risen from 43.88 to 54.49 kg annually. This surge has led to an expansion of fish farming activities, particularly within small-scale enterprises. However, a significant challenge faced by these farmers is the high cost of commercial fish feed, which accounts for 60-80% of total production expenses. These costs are further amplified by the reliance on expensive and environmentally harmful imported ingredients such as fishmeal and soybean meal. In response to these challenges, this study focuses on a community service initiative conducted at KUPS Fisheries in Tanjung Sangalang, Pulang Pisau, Central Kalimantan. The project aimed to provide local fish farmers with essential skills in feed production and the utilization of floating net cages for sustainable fish farming. Through training and hands-on practice, participants were introduced to cost-effective, locally sourced alternatives for fish feed, reducing dependency on expensive imports. The initiative also promoted environmentally friendly practices, contributing to both the economic and ecological sustainability of small-scale fish farming in the region.